Seismic-stratigraphic architecture of the oligocene-pliocene camaná formation, southern peruvian forearc - Alván A. (2017)
The Camaná-Mollendo Basin is an active-margin depression ~NW-SE elongated, which is located in the forearc of southern Perú and extends from the Coastal Cordillera to the Perú-Chile Trench. This basin consists of a grabens and half-graben complex, filled with deltaic and fluvial sedimentary rocks of the Oligocene-Pliocene Camaná Formation (~500 m thick). An integration of compiled onshore stratigraphic logs, reinterpreted 2D seismic offshore information, sediment provenance data, and previous zircon U-Pb geochronology on volcanic reworked ash supports a refined tectono-chronostratigraphic framework for the whole Camaná-Mollendo Basin fill. To complete this integration we needed firstly to elaborate a geological reinterpretation of seismic offshore data and highlight their most prominent features (i.e., erosive surfaces). This step allowed establishing a first correlation between onshore and offshore deposits of Camaná Formation by means of their sequence boundaries, giving as result a consistent division for Camaná Formation: (i) “CamA Unit” (coarse-grained deltas) and (ii) “CamB Unit” (fluvial deposits). CamA Unit is further subdivided into three subunits based on minor erosive surfaces (i.e., A1: Oligocene, A2: Early Miocene, and A3: Middle Miocene). CamA reflects prograding geometry (subunits A1 and A2) as well as onlapping geometry (subunit A3). CamB Unit (Late Miocene to Pliocene) consists of high-energy hyperpycnal flows composed of fluvial conglomerates in onshore, which very possibly changes to progradational deltaic in offshore. Each one of these units and subunits extends offshore and preserves similarities in depositional geometry and sequence boundaries with Camaná Formation onshore. Subunits A1 and A2 observed in offshore are grouped in this paper as “A1+A2” (Oligocene to Middle Miocene) because they show similar progradational geometry and it is difficult to differentiate them from each other. A regressive systems tract (RST) represents these subunits. These deposits reach up to ~2.5 km thick, and they are intensely affected by normal faulting associated to pinch-out depositional geometry. Strata of subunit A3 (Middle Miocene) reflect a transgressive systems tract (TST), and blanket the entire basin with fine-grained sediments. These deposits are up to ~1 km thick, being less affected by synsedimentary tectonic and show minor effects of synsedimentary tectonics. Finally, deposition of CamB Unit (Late Miocene to Pliocene) occurred during a new regressive systems tract (TST), which turned to progradational geometry similar to deltaic deposits in offshore, and according to seismic lines they are much less affected by synsedimentary faulting. Stratigraphic boundaries between “A1+A2” and A3, and between A3 and CamB observed in onshore outcrops are used here as tools to differentiate, correlate and predict the main depositional geometries in offshore. High-frequency seismic reflectors represent such boundaries and support divisions and subdivisions within Camaná Formation. These boundaries are also used to define depocentres of Camaná Formation along the entire Camaná-Mollendo Basin, where the thickests are located in the proximity of the large river mouths (e.g., Planchada, Camaná, and Punta de Bombón). Strata of subunits “A1+A2” are considered as potential reservoir for hydrocarbon due to their high rate of sediment accumulation. Deposits of A3 are transgressive and they are considered as potential potential seal rock. Structurally, Camaná-Mollendo Basin is composed of graben and half-graben components ~NW-SE-oriented, typical of a trantensional tectonic regime. © 2017, Servicio Nacional de Geologia y Mineria. All Rights Reserved.